A Review on the Artificial Bee Colony & Clahe Based Hybrid Hough Transform For Efficient Lane Detection (International Journal of Engineering and Computer Science, 2017)
This paper represents that lane coloration has become popular in real time vehicular ad-hoc system. Lane detection is normally helpful to localize path limits, determine undesired lane variations, and to enable approximation of the upcoming geometry of the road. There are different types of methods that are used for detecting lines, curves and ellipses i.e. hough transform, clustering and curve fitting. The overall objective of this paper is to providing better performance in lane coloration algorithm. The methods developed till now are working effectively as well as giving good results. Keywords: Lane Detection, Hough Transform, Clustering, Curve Fitting